PENGARUH KUALITAS PRODUK DAN EKUITAS MEREK TERHADAP LOYALITAS PELANGGAN PT. LOTTE INDONESIA - Chaeru Syahru Ramdani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
he food and beverage industry is growing rapidly, the food and beverage industry demands the implementing parties of the food and beverage industry to improve the quality of their services. With good service, it is hoped that satisfaction will be achieved. Therefore, it is necessary to analyze the resulting quality. The quality or quality of a good product will lead to satisfaction. PT. Lotte Indonesia is a company engaged in the supervision of snacks that is well known by the people in Indonesia, especially in the Greater Jakarta area. The sample used in this study were 80 customers. The analysis used in this study includes descriptive techniques used to describe the object of research, how the profile of PT. Lotte Indonesia describes the tabulation results, and the technique of inferential statistical analysis is carried out using Multiple Linear Regression Analysis. Multiple Linear Regression Analysis is useful in estimating the value of the dependent variable by using more than one independent variable and using the help of computer analysis tools through the IBM SPSS 21 program. Simultaneously, the variables of product quality and brand equity have a significant positive effect on customer loyalty. This is evidenced by the F-count (F-Statistics) of 5.860 with a significance level (probability number) of 0.032 <0.05. while the F-Table with df1 = 2 and df2 = 7 at the 0.05 level is 4.74, thus F-Calculate (5,860) > F-Table (4.74) means that all independent variables jointly have a significant effect on the dependent variable, so it can be concluded that there is a significant positive influence there is customer loyalty PT. Lotte Indonesia (xylitol). While brand equity partially has a negative effect on customer loyalty PT. Lotte Indonesia (xylitol). Because from the results of the analysis that has been carried out, namely tcount -0.463 < ttable 2.6403, it is not in the area of ??acceptance of Ho (accepted), so the brand equity variable has no effect on customer loyalty with a 95% confidence level.